Membangun Assesment Akademik Anak Berkebutuhan Khusus Di Sekolah Terintegrasi - Opi Andriani; Apala Apala; Khoirul Zikri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The aim of this research is to determine the Bulding Assessment Holistic of Children with Special Needs in Integrated Schools. The method used in this research is inductive qualitative research, meaning that the researcher provides problems that arise from the data or is left open for interpretation. Data collection techniques include: observation, interviews, and documentation. The research subjects are teachers. The results of interviews conducted by researchers with teachers at SDN 195/VIII Wirotho Agung show that integrated schools for children with special needs (ABK) are inclusive schools that provide educational services for ABK without paying attention to their physical, intellectual, social and emotional conditions.